Antimicrobial efficacy of sodium hypochlorite, saline, and Er, Cr:YSGG laser-assisted disinfection in root canal treatment of primary molars: An in vivo study - Neha Chauhan; Gyanendra Kumar; Mridula Goswami; Smriti Johar; Abha Sharma (Wolters Kluwer Medknow Publications, 2023)
Aim: The aim of the study was to compare the antimicrobial efficacy of sodium hypochlorite (NaOCl), Saline, and Er, Cr:YSGG laser-assisted disinfection through microbiological analysis in root canal treatment of primary molars. Materials and Methods: Forty-five primary teeth were selected for this study as per the inclusion and exclusion criteria in the age group of 4-8 years and then randomly allocated to Three Groups A, B, and C. In Group A, during root canal treatment, irrigation was done using NaOCl, in Group B, laser-assisted disinfection was done using Er, Cr:YSGG laser, and in Group C, saline was used as an irrigating agent. This was followed by obtaining pre- and postirrigation samples from the canals for microbiological investigation in all the groups. Data analysis was performed using Statistical Package for the Social Science-21 (SPSS-21). Results: NaOCl was more effective against aerobic bacteria while Er, Cr:YSGG laser was more effective against anaerobic bacteria when used for disinfection in root canal treatment. There was a significant difference among the three groups (P > 0.05). Conclusion: The study showed that NaOCl and Er, Cr:YSGG laser have antimicrobial effects when used for disinfection in root canal treatment of primary teeth. Moreover, the study also shows that Er, Cr:YSGG laser may be used as a valuable tool for laser-assisted disinfection in root canal treatment of primary teeth.